Geotectonic Configuration of Kulon Progo Area, Yogyakarta - Syafri, Ildrem; Budiadi, E.; Sudradjat, A. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i4.168Kulon Progo Mountain, located west of Yogyakarta, is known as a unique morphological expression of an elongated dome frequently called âoblong domeâ. The structural elements occurring in Kulon Progo Mountain were predominated by a radial pattern. Applying a quantitative method to measure various morphometric elements however, revealed that the regional geotectonic pattern apparently controlled the development of Kulon Progo Mountain. A general picture of the tectonics showed that the mountain building of Kulon Progo was not solely predominated by a vertical undation force; instead it was closely related to the general geotectonics operating in the area. The macro morphological analysis using various types of satellite imageries augmented with field visits unraveled three regional tectonic stages controlled the development of Kulon Progo Mountain. Those are Meratus, Sunda, and Java trends, operating in SW-NE, NNW-SSE, and E-W directions respectively.